2000
DOI: 10.1101/gr.10.7.924
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Genomic Organization, Developmental Regulation, and a Knock-out Mutant of a Novel Leu-rich Repeats-containing G Protein-coupled Receptor (DLGR-2) from Drosophila melanogaster

Abstract: After screening the Berkeley Drosophila Genome Project database with sequences from a recently characterized Leu-rich repeats-containing G protein-coupled receptor (LGR) fromDrosophila (DLGR-1), we identified a second gene for a different LGR (DLGR-2) and cloned its cDNA. DLGR-2 is 1360 amino acid residues long and shows a striking structural homology with members of the glycoprotein hormone [thyroid-stimulating hormone (TSH); follicle-stimulating hormone (FSH); luteinizing hormone/choriogonadotropin (LH/CG)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…The observed ligand signaling of different chimeric receptor mutants consisting of human LH receptor and fly LGR2 also suggested that fly LGR2 likely belongs to the same subgroup of LGRs together with glycoprotein hormone receptors and fly LGR1 (8). Despite the lack of knowledge on the endogenous ligand(s) for the fly LGR2, understanding of the signaling pathway for this orphan receptor could facilitate future identification of its ligands using bioinformatic and biochemical approaches (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed ligand signaling of different chimeric receptor mutants consisting of human LH receptor and fly LGR2 also suggested that fly LGR2 likely belongs to the same subgroup of LGRs together with glycoprotein hormone receptors and fly LGR1 (8). Despite the lack of knowledge on the endogenous ligand(s) for the fly LGR2, understanding of the signaling pathway for this orphan receptor could facilitate future identification of its ligands using bioinformatic and biochemical approaches (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate the evolution of a large family of the leucine-rich repeat-containing, G protein-coupled receptors (LGRs) with at least seven members in mammals, including the well studied glycoprotein hormone receptors (3,4) and LGR4 -7 (5,6). In addition, homologous LGRs were found in fly (LGR1 and LGR2) (7,8), nematode (nLGR) (9), sea anemone (10), and snail (11). These genes can be divided into three subgroups, each with unique structural characteristics (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing RK and the cells that express it has been impeded in the fly by the complexity of the rk gene locus. Two splice variants, rk-RA and rk-RF, with different 59 start sites, are predicted from the rk genomic sequence, and other transcripts have been identified (Eriksen et al 2000;Nishi et al 2000). The longest variant, rk-RA, has highly conserved, putative regulatory elements throughout its first, large intron and multiple possible translation start sites, the first of which is preceded by six out-of-frame ATG triplets in the putative 59 UTR (Eriksen et al 2000).…”
mentioning
confidence: 99%
“…Two splice variants, rk-RA and rk-RF, with different 59 start sites, are predicted from the rk genomic sequence, and other transcripts have been identified (Eriksen et al 2000;Nishi et al 2000). The longest variant, rk-RA, has highly conserved, putative regulatory elements throughout its first, large intron and multiple possible translation start sites, the first of which is preceded by six out-of-frame ATG triplets in the putative 59 UTR (Eriksen et al 2000). Direct knock-in of the Gal4 transgene into the predicted start site by homologous recombination resulted in no detectable expression of Gal4 (F. Diao and B. H. White, unpublished observations).…”
mentioning
confidence: 99%